2017
DOI: 10.3390/bioengineering4020050
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Sugarcane Bagasse by Halogeometricum borinquense Strain E3 for Biosynthesis of Poly(3-hydroxybutyrate-co-3-hydroxyvalerate)

Abstract: Sugarcane bagasse (SCB), one of the major lignocellulosic agro-industrial waste products, was used as a substrate for biosynthesis of polyhydroxyalkanoates (PHA) by halophilic archaea. Among the various wild-type halophilic archaeal strains screened, Halogeometricum borinquense strain E3 showed better growth and PHA accumulation as compared to Haloferaxvolcanii strain BBK2, Haloarcula japonica strain BS2, and Halococcus salifodinae strain BK6. Growth kinetics and bioprocess parameters revealed the maximum PHA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 51 publications
2
29
0
1
Order By: Relevance
“…In most cases, scl-PHA producing microbes convert simple carbon sources like sugars, alcohols or lipids via acetyl-CoA towards 3HB; production of 3HV or 4HB normally requires structurally related precursor substrates such as the 3HV-precursors propionic acid [27], valeric acid [28], levulinic acid [29][30][31], the cocktails of ozonolytically splitted fatty acids [32] or non-oxygenated polyethylene wax [33], or 4HB-precursors like γ-butyrolactone (GBL), 4HB sodium salt, or 1,4-butanediole [34,35]. Among extremophilic Archaea, a number of strains such as Haloferax mediterranei [36] or Halogeometricum borinquense [37] have been identified, which produce copolyesters of 3HB and 3HV (PHBHV) from simple, structurally unrelated substrates such as carbohydrates or glycerol, which in turn saves on precursor costs for copolyester synthesis. Among eubacteria, PHA copolyester production from unrelated substrates is a scarce feature and reported, e.g., for the Gram-positive strain Bacillus licheniformis PL26 [5] and the Gram-negative strain Hydrogenophaga pseudoflava [38].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, scl-PHA producing microbes convert simple carbon sources like sugars, alcohols or lipids via acetyl-CoA towards 3HB; production of 3HV or 4HB normally requires structurally related precursor substrates such as the 3HV-precursors propionic acid [27], valeric acid [28], levulinic acid [29][30][31], the cocktails of ozonolytically splitted fatty acids [32] or non-oxygenated polyethylene wax [33], or 4HB-precursors like γ-butyrolactone (GBL), 4HB sodium salt, or 1,4-butanediole [34,35]. Among extremophilic Archaea, a number of strains such as Haloferax mediterranei [36] or Halogeometricum borinquense [37] have been identified, which produce copolyesters of 3HB and 3HV (PHBHV) from simple, structurally unrelated substrates such as carbohydrates or glycerol, which in turn saves on precursor costs for copolyester synthesis. Among eubacteria, PHA copolyester production from unrelated substrates is a scarce feature and reported, e.g., for the Gram-positive strain Bacillus licheniformis PL26 [5] and the Gram-negative strain Hydrogenophaga pseudoflava [38].…”
Section: Introductionmentioning
confidence: 99%
“…H. volcanii produces PHB up to 7% of its cell dry weight when grown on media containing 250 g/L salts, 10 g/L glucose and 1 g/L yeast extract (Fernandez-Castillo et al 1986). An additional report for H. volcanii mediated PHA accumulation from sugarcane bagasse substrate, a fibrous leftover by-product of the sugarcane industry, was recently published (Salgaonkar and Bragança 2017). In contrast, another study reported no detection of PHB from H. volcanii (Legat et al 2010).…”
Section: Biotechnological Potential Of H Volcaniimentioning
confidence: 99%
“…As demonstrated in the case of Hfx. mediterranei and Halogeometricum borinquense, such organisms produce poly(3HB-co-3HV) without the need for 3HV-related precursor compounds; feeding these strains with simple pure sugars, 116 hydrolyzed bagasse, 117 or glycerol 74 is sufficient to make them produce copolyesters. Only recently, copolyester production from inexpensive unrelated substrates was detected also in eubacteria, when Bacillus licheniformis PL26 was shown to accumulate poly(3HB-co-3HV) from crude glycerol from the biodiesel production.…”
Section: Hv-containing Heteropolyestersmentioning
confidence: 99%